Evidence‐based policy choices for efficient and equitable cervical cancer screening programs in low‐resource settings - Campos, Nicole G. (Cancer Med, 2017)
Women in developing countries disproportionately bear the burden of cervical cancer. The availability of prophylactic vaccines against human papillomavirus (HPV) types 16 and 18, which cause approximately 70% of cervical cancers, provides reason for optimism as roll‐out begins with support from Gavi, the Vaccine Alliance. However, for the hundreds of millions of women beyond the target age for HPV vaccination, cervical cancer screening to detect and treat precancerous lesions remains the only form of prevention. Here we describe the challenges that confront screening programs in low‐resource settings, including (1) optimizing screening test effectiveness; (2) achieving high screening coverage of the target population; and (3) managing screen‐positive women. For each of these challenges, we summarize the tradeoffs between resource utilization and programmatic attributes. We then highlight opportunities for efficient and equitable programming, with supporting evidence from recent mathematical modeling analyses informed by data from the PATH demonstration projects in India, Nicaragua, and Uganda.